Ewolucja zasad zadośćuczynienia w polskim prawie cywilnym - Mozgiel-Wiecha, Kinga (PRAWO i WIĘŹ, 2025)
The paper presents the evolution of the principles of reparation by referring to its origins, which still date back to Roman law. The process of implementation of the rules indicated by Roman law and German law is presented. Then, the evolution of the principles of compensation in Polish civil law from the early Polish legislation through the period of partitions, the years of World War I and World War II, to the present legislation is presented. The core of the paper is a consideration of the evolution and perception of the principles of compensation over the years. It indicated how Polish legislation has drawn on and modelled itself on other European legislation, creating its own legislation. The paper also indicated how the perception of redress by the greatest representatives of European jurisprudence has changed. Referring to modern times, the provisions of Article 445, Article 446 § 4, and Article 448 of the Civil Code were analysed. In particular, it shows the most recent jurisprudence on compensation for the death of a loved one, a provision that is currently widely commented on in doctrine and jurisprudence. Financial compensation in the light of the rules of Article 446 § 4 is still not well established, and increasing inflation directly affects the amount of compensation awarded for the death of a close relative.